Sistem Informasi Persebaran ODP (Optical Distribution Point) Telkom Pemalang Berbasis WebGIS dengan Leaflet - Anis Supriatin; Iskandar Fitri; Sari Ningsih (SMATIKA JURNAL, 2021)
This study aims to design an information system that can assist Telkom's ODP (Optical Distribution Point) data processing. ODP is a fiber optic support device to help distribute core optics to several Indihome customers. With this information system, it can make it easier for the Indihome admin and sales force to know the ODP distribution points that are still usable or full. The information system for the distribution of ODP Telkom Pemalang based on WebGIS (Website Geographic Information System) was created using a leaflet library, codeigniter 3 framework and mysql database. Leaflet libraries are used to build web-based interactive maps that support desktop and mobile platforms. The results of this study are the use of L.map to generate maps and view settings for locations on the map. Besides that, it also uses L.marker as a marker of the point and ODP information at the location using latitude and longitude. The results of the L.map test were carried out at several longitude and latitude points at several location points in Pemalang district and generated views that match the location. Usability test results from this system produced effectiveness of 4,30 and efficiency of 4,16 on a scale 1-5.